Quercetin induces cell cycle arrest and apoptosis in CD133(+) cancer stem cells of human colorectal HT29 cancer cell line and enhances anticancer effects of doxorubicin - Atashpour, Shekoufeh (Iran J Basic Med Sci, 2015)
OBJECTIVE(S): The colorectal cancer stem cells (CSCs) with the CD133(+) phenotype are a rare fraction of cancer cells with the ability of self-renewal, unlimited proliferation and resistance to treatment. Quercetin has anticancer effects with the advantage of exhibiting low side effects. Therefore, we evaluated the anticancer effects of quercetin and doxorubicin (Dox) in HT29 cancer cells and its isolated CD133(+) CSCs. MATERIALS AND METHODS: The CSCs from HT29 cells were isolated using CD133 antibody conjugated to magnetic beads by MACS. Anticancer effects of quercetin and Dox alone and in combination on HT29 cells and CSCs were evaluated using MTT cytotoxicity assay and flow cytometry analysis of cell cycle distribution and apoptosis induction. RESULTS: The CD133(+) CSCs comprised about 10% of HT29 cells. Quercetin and Dox alone and in combination inhibited cell proliferation and induced apoptosis in HT29 cells and to a lesser extent in CSCs. Quercetin enhanced cytotoxicity and apoptosis induction of Dox at low concentration in both cell populations. Quercetin and Dox and their combination induced G2/M arrest in the HT29 cells and to a lesser extent in CSCs. CONCLUSION: The CSCs were a minor population with a significantly high level of drug resistance within the HT29 cancer cells. Quercetin alone exhibited significant cytotoxic effects on HT29 cells and also increased cytoxicity of Dox in combination therapy. Altogether, our data showed that adding quercetin to Dox chemotherapy is an effective strategy for treatment of both CSCs and bulk tumor cells.